2020
DOI: 10.3390/su12176719
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yoga Practice on Personality, Body Image and Lactate. Pilot Study on a Group of Women from 40 Years

Abstract: Yoga techniques are increasingly popular all over the world. This discipline provides benefits both in relation to particular psychological disorders, such as anxiety disorders or those related to stress, but also in relation to certain clinical frameworks that involve significant life changes of people. Some studies have shown that this practice brings relevant benefits regarding cognitive functions such as memory and attention. The aim of this study was to verify, in women over 40 years of age, whether the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Being ready and vigilant in order to respond to an offense, to shoot for a basket, to go off to shoot, etc. in addition to specific muscle characteristics, can make a difference [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Being ready and vigilant in order to respond to an offense, to shoot for a basket, to go off to shoot, etc. in addition to specific muscle characteristics, can make a difference [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, lactate is no longer considered only as a metabolic waste product, it has been observed that it plays a role at the level of the central nervous system, both directly and indirectly. Research shows that lactate is an important energy substrate in astrocytes, and at the same time plays a protective or modulatory role at the level of primary cortical areas (such as M1, V1 or S1) [46][47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…According to research, agreeableness might lead to higher selfefficacy (Coco et al, 2020). Individual SE is positively connected with extraversion and adversely correlated with neuroticism, according to some studies (Schmitt, 2007).…”
Section: Big Five Personality Traits and Entrepreneurial Self-efficacymentioning
confidence: 99%
“…Openness transforms requests into challenges to be met, resulting in increased level of engagement in different tasks and their self-efficacy ( Sanchez-Cardona et al, 2012 ; Neneh, 2020 ). According to research, agreeableness might lead to higher self-efficacy ( Coco et al, 2020 ). Individual SE is positively connected with extraversion and adversely correlated with neuroticism, according to some studies ( Schmitt, 2007 ).…”
Section: Literature Reviewmentioning
confidence: 99%